Neutrophil in Reverse Migration: Role in Sepsis - Ji, Jingjing; Fan, Jie (Frontiers in Immunology, 2021)
Sepsis is life-threatening organ dysfunction caused by a dysregulated host response to infection. During the development and progression of sepsis, polymorphonuclear neutrophils (PMNs) are the most abundantly recruited innate immune cells at sites of infection, playing critical roles in the elimination of local infection and the healing of injury. PMN reverse migration (rM) describes the phenomenon in which PMNs migrate away from the inflammatory site back into the vasculature following the initial PMN infiltration. The functional role of PMN rM within inflammatory scenarios requires further exploration. Current evidence suggests that depending on context, PMN rM can be both a protective response, by facilitating an efficient resolution to innate immune reaction, and also a tissue-damaging event. In this review, we provide an overview of current advancements in understanding the mechanism and roles of PMN rM in inflammation and sepsis. Comprehensive understanding of PMN rM may allow for the development of novel prophylactic and therapeutic strategies for sepsis.